Increasing the Odds: Applying Emergentist Theory in Language Intervention. - Polla, Gerard H. (Language, Speech & Hearing Services in Schools, 2011)
Purpose: This review introduces emergentism, which is a leading theory of language development that states that language ability is the product of interactions between the child's language environment and his or her learning capabilities. The review suggests ways in which emergentism provides a theoretical rationale for interventions that are designed to address developmental language delays in young children.